A biomimetic‐structured wood‐derived carbon sponge with highly compressible and biocompatible properties for human‐motion detection. Issue 6 (17th January 2020) - Chen, Yipeng; Hu, Lintong; Li, Caicai; Dang, Baokang; Sun, Qingfeng; Zhai, Tianyou; Li, Huiqiao
Abstract: Piezoresistive sensors, as an indispensable part of electronic and intelligent wearable devices, are often hindered by nonrenewable resources (graphene, conventional metal, or silicon). Biomass‐derived carbonaceous materials boast many advantages such as their light weight, renewability, and excellent chemical stabilization. However, a major challenge is that the strength and resilience of carbon‐based piezoresistive materials still falls short of requirements due to their random microarchitectures which cannot provide sufficiently good stress distribution. Encouraged by the excellent compressible properties and extraordinary strength of the Thalia dealbata stem, we propose a wood biomass‐derived carbon piezoresistive sensor with an artificial interconnected lamellar structure like the stem itself. By introducing a freezing‐induced assembly process, a wood‐based, completely delignified, nano‐lignocellulose material can be built into a "bridges supported lamellar" type architecture, where subsequent freeze‐drying and pyrolysis results in carbon aerogel monoliths. The resultant bioinspired carbon sponge has high compressibility and strength, of the order of two to five times higher than that of conventional metal, carbon, and organic materials. Combined with excellent biocompatible properties and chemical durability, these are useful properties for intelligent wearable devices and human‐motion detection. Abstract : Inspired by the excellent compressible properties and extraordinary strength of Thalia dealbata stem, we developed a biomass fibre‐to‐carbonsponge strategy for fabricating highly lightweight and compressible wood‐derived carbon sponge directly from natural wood fiber via a down‐top approach. The biomass‐derived carbon sponge shows outstanding mechanical properties and sensitive electrical responses as a strain sensor, which are highly expected for intelligent wearable devices and human‐motion detection.